2020
DOI: 10.1111/jce.14502
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin vs non‐vitamin K oral anticoagulants for left atrial appendage thrombus: A meta‐analysis

Abstract: Introduction Novel oral anticoagulants (NOACs) are commonly used for thromboembolic risk reduction and treatment of pulmonary embolism and deep venous thrombosis. However, data regarding their efficacy and safety in comparison to warfarin for left atrial appendage thrombus is limited. Methods A comprehensive literature search in PubMed, Google Scholar, and Cochrane Review from inception to 30 October 2019 was performed. Studies reporting clinical outcomes comparing warfarin vs NOACs were included. Two investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…Furthermore, no significant difference was observed in terms of SEE and failure of LV thrombus resolution in patients treated with DOACs compared to VKAs. Similar results have also been demonstrated in patients with other forms of cardiac thrombus like left atrial appendage thrombus 29 . With a growing body of evidence and increasing interest in DOACs utilization, our study results are vital in demonstrating the safety and efficacy of DOACs in patients with LV thrombus.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Furthermore, no significant difference was observed in terms of SEE and failure of LV thrombus resolution in patients treated with DOACs compared to VKAs. Similar results have also been demonstrated in patients with other forms of cardiac thrombus like left atrial appendage thrombus 29 . With a growing body of evidence and increasing interest in DOACs utilization, our study results are vital in demonstrating the safety and efficacy of DOACs in patients with LV thrombus.…”
Section: Discussionsupporting
confidence: 79%
“…The significantly lower odds of overall bleeding with DOAC's (compared to VKA's) observed in our study could have been primarily driven by reduced rates of minor bleeding events (and numerical lower major bleeding events rates with DOAC's—finding that did not reach statistical significance). Furthermore, the pooled incidence of overall bleeding and major bleeding were 5.6% and 1.1% with DOACs, respectively; findings significantly lower to patients with LAA thrombus in a prior study (overall bleeding: 12.1%; major bleeding: 0.7%) 29 …”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Finally, thrombus resolution was achieved in 83.3% and 81.8% of patients treated with dabigatran and rivaroxaban, respectively. Some other studies also confirmed the efficacy of NOACs in the treatment of LAAT [16][17][18]. However, standard-dose NOACs were commonly used in those investigations.…”
Section: Discussionmentioning
confidence: 84%